Factors influencing first-service conception and overall pregnancy rates in commercial beef heifers - Utter, S.D.; Houghton, P.L.; Corah, L.R.; Simms, D.D.; Spire, M.F.; Butine, M.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Commercial beef heifers (n=1863) from 16 different sources were used to evaluate the influence of management practices and biological traits on first-service conception and overall pregnancy rates. Frame score, initial weight, overall ADG, body condition score, reproductive tract score, source, AI technician, and AI sire significantly influenced first-service conception. Overall pregnancy rates were influenced by frame score, body weight, and ADG.
Keywords: Beef; Beef heifers; First-service conception; Pregnancy rates